EFFICACY OF FUNGICIDES AND TRICHODERMA VIRIDE AGAINST FUSARIUM OXYSPORUM F. SP. CUBENSE IN- VITRO - ANITA KUMARI; RAHUL KUMAR; HARSH KUMAR (The Bioscan, 2014)
Fusarium wilt of banana is one of the most destructive diseases of banana worldwide. Four fungicides Mancozeb, Saaf, Carbendazim and Cuprozin in three different concentrations (0.01%, 0.02% and 0.03%) and one biocontrol agent Trichoderma viride were evaluated against mycelial growth of the causal pathogen Fusarium oxysporum f. sp. cubense in-vitro by poison food and dual culture techniques respectively. Observations were taken at 24 hours intervals up to 192 hours for the assessment of their inhibitory effects. Among them, Carbendazim at its all concentrations was found to be the most effective against the pathogen followed by Saaf. Carbendazim at 0.01% and 0.02% inhibited fungus at 1.66mm and 1.16mm of mycelial growth respectively after 72 hours of treatment, while at 0.03% concentration it inhibited fungus growth at 0.99mm after 48 hours only. The biocontrol agent Trichoderma viride in dual culture with pathogen completely inhibited its mycelial growth. The pathogen fungus continued to increase up to 192 hours showing a radial growth of 38.99mm in control but in dual culture it showed growth of 17.50mm up to 120 hours only and after that there was no further growth. Thus, fungicide Carbendazim and biocontrol agent Trichoderma viride can be used for the amelioration and control of wilt disease in banana.